A Konflik sosial dalam film “Black Panther” karya Ryan Coggler: Kajian sosiologi sastra - Jumardan, Sulis (Maliki Interdisciplinary Journal, 2024)
Social issues are problems or challenges that affect individuals or society at large, often involving inequality, injustice, or human rights violations. Various factors, including cultural, economic, political, and environmental, can contribute to social issues. This research aims to present the social issues depicted in the film Black Panther. This study uses a descriptive qualitative method. The data for this research includes conversations, expressions, and speech patterns in the film Black Panther. The data collection techniques involve watching, listening, and noting. The social issues in the film Black Panther are (1) Racism of white people towards black people. (2) Acts of robbery. (3) Acts of murder. (4) Power struggle conflicts.